Crises and capital controls in small open economies: a stock–flow consistent approach - Hamid Raza; Bjorn Runar Gudmundsson; Gylfi Zoega; Mikael Randrup Byrialsen (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
This paper attempts to explain the role of capital inflows in creating economic booms and busts in a small open economy with sovereign currency. We develop a stock–flow consistent (SFC) model for a small open economy while relying on the experience of the Icelandic crisis. We demonstrate the destabilising effects of capital inflows on the economy by allowing for a sudden stop, and also discuss the role of capital controls as a policy response in the event of a crisis due to sudden stops. Finally, we discuss the policy implications of our results in order to tackle the destabilising effects associated with financial flows in a small economy.
Keywords: E12; F32; F38; F41; 330; post-Keynesian; stock–flow consistent; monetary policy; capital controls; sudden stops; financial crisis